Karakteristik Baduta dan Analisis Pengembangan Aplikasi STOP STUNTING dalam Upaya Penurunan Kasus Stunting - Dwi Noerjoedianto; Ismi Nurwaqiah Ibnu; Arnild Augina Mekarisce (Universitas Medan Area, 2022)
Stunting is a chronic malnutrition problem caused by insufficient intake for a long time. There has been an increase in stunting in Indonesia, especially the prevalence of stunting under five in Jambi Province is higher than the national figure of 37.9%. The implementation of nutrition interventions has not been integrated, from the planning process to evaluation at the central, regional and village levels. As a result, the coverage and quality of various basic services is less than optimal. Therefore, this study aims to analyze application development as an effort to monitor the evaluation of health workers. The method used is a descriptive method with a survey approach, the population in this study is health workers, cadres, midwives from two pilot health centers in West Tanjab, namely Pijoan Baru Health Center and Sungai Saren Health Center with a total sampling of 18 people. The results of the study concluded that there are still a lot of data on infants and mothers that are difficult to monitor, through the STOP STUNTING application on the toddler monitoring feature added warnings (danger signs on toddler growth) (83.3%), symptoms of hyperthyroidism at birth (72.2%), data completeness of the baby at birth (77.78%), early initiation of breastfeeding and exclusive breastfeeding (88.89%), and cognitive development of toddlers (66.67%). In the features of pregnant women, the identity of the primary health center is needed (88.89%), participation in the class of pregnant women (66.67%), consumption of blood-added tablets (77.78%), and a history of infectious diseases of pregnant women (55.56%) , and reporting the results of the application in the form of a cohort table (88.9%).